Controlling-Supportive Homework Help Partially Explains the Relation between Parents' Math Anxiety and Children's Math Achievement - Fraulein Retanal; Nichole B. Johnston; Sabrina M. Di Lonardo Burr; Andie Storozuk; Michela DiStefano; Erin A. Maloney (MDPI AG, 2021)
Previous research has shown that math homework help of higher-math-anxious parents impedes children's math learning and facilitates the development of math anxiety. In the present study, we explored a possible explanation for this phenomenon by examining the relations between parents' math anxiety, their math homework-helping styles (i.e., autonomy- and controlling-supportive), and their child's math achievement. Parents of children ages 11 to 14 completed an online survey. Using path analysis, we examined the relations among parental factors (i.e., math anxiety, math ability, and homework-helping styles) and child math achievement. Parents' math anxiety was positively related to both autonomy-supportive and controlling-supportive math homework-helping styles. Notably, controlling-supportive style partially mediated the relation between parents' math anxiety and their children's math achievement. Thus, it is possible that the use of a controlling-supportive math homework-helping style may explain why the homework help offered by higher-math-anxious parents is detrimental to their children's math learning. Identifying negative relations between parent factors and children's math outcomes is crucial for developing evidence-based math learning interventions.